Efecto de la autoeficacia de la conducta proambiental en la intención de comportamiento de consumo responsable de los centennials - García Morausky, Lisveth Rosa (2025)
To tackle climate change, it is essential that humans modify their consumption habits. To do so, it is extremely important to understand the factors that influence behavior and the leading role that centennials are playing. Therefore, the objective of this research is to demonstrate the relationship between self-efficacy of pro-environmental behavior and centennials' intention to engage in responsible consumption behavior. To this end, a quantitative, non-experimental, cross-sectional correlational design was used, as well as a questionnaire as an instrument. In addition, a sample of 354 centennials was determined through non-probability convenience sampling. It was concluded that there is a significant relationship between self-efficacy in pro-environmental behavior and the intention to engage in responsible consumption behavior among centennials.